2016
DOI: 10.12771/emj.2016.39.3.69
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Individuals over Age 80: Unattended Issue in Clinical Practice

Abstract: Original Article Ewha Med J 2016;39(3):69-75 http://dx. Objectives:To assess the current state of anemia evaluation in the elderly over 80 years of age. Methods: Patients who were more than 80 years old and visited Dongguk University Ilsan Hospital from April 2005 to February 2014 were included. Statistical analysis were assessed using the logistic regression model. Results: Total 548 patients, who had anemia according to WHO criteria, were identified. The median age was 85 years old (range, 82 to 99 years) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Han et al [8] analyzed healthy individuals who underwent routine medical checkup in a single center and showed that mild anemia, de ned as having a hemoglobin level between 10.0 g/dL and 12.9 g/dL in men and 10.0 g/dL and 11.9 g/dL in women, is a risk factor for cancer and cardiovascular death in the elderly population. Jeong et al [24] also showed a high incidence of anemia in the population aged 80 years and more, and most of them were anemic from unknown reasons, which was closely related to malignancy as analyzed by routine medical checkup of laboratory data. These studies are small community-based cross-sectional studies within a selected population and are limited in re ecting the general Korean population.…”
Section: Discussionmentioning
confidence: 98%
“…Han et al [8] analyzed healthy individuals who underwent routine medical checkup in a single center and showed that mild anemia, de ned as having a hemoglobin level between 10.0 g/dL and 12.9 g/dL in men and 10.0 g/dL and 11.9 g/dL in women, is a risk factor for cancer and cardiovascular death in the elderly population. Jeong et al [24] also showed a high incidence of anemia in the population aged 80 years and more, and most of them were anemic from unknown reasons, which was closely related to malignancy as analyzed by routine medical checkup of laboratory data. These studies are small community-based cross-sectional studies within a selected population and are limited in re ecting the general Korean population.…”
Section: Discussionmentioning
confidence: 98%
“…Reference values represent average levels with standard deviations, and the low hemoglobin levels in the older population might be considered as the standard reference values for this population group. Some reports concluded that this decrease in hemoglobin levels might be one of the consequences of the normal aging process; hence, the criteria for anemia should be different in this population [17,[22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of anemia ranged from 12% to 17%. These differences might be attributed to the diversity of the subjects and cohorts [3,8,23,25,28]. Studies conducted in nursing home-and hospital-based populations have shown signi cantly higher prevalence of anemia and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Reference values represent average levels with standard deviations, and the low hemoglobin levels in the older population might be considered as the standard reference values for this population group. Some reports concluded that this decrease in hemoglobin levels might be one of the consequences of the normal aging process; hence, the criteria for anemia should be different in this population [17,[22][23][24][25]. However, many reports also showed that anemia in older persons is related to the presence of underlying health conditions and is therefore associated with high mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of anemia ranged from 12% to 17%. These differences might be attributed to the diversity of the subjects and cohorts [3,8,23,25,28]. Studies conducted in nursing home-and hospital-based populations have shown significantly higher prevalence of anemia and morbidity.…”
Section: Discussionmentioning
confidence: 99%